Photochromism of 2H-naphtho[1, 2-b]pyran-4-carboxylates. (April 2023) - Graça, Vânia; Berthet, Jérôme; Delbaere, Stephanie; Coelho, Paulo J.
Abstract: New 2 H -naphthopyrans substituted at C-4 by a carboxylate group were synthesized through the one-pot acid-catalyzed reaction of naphthols with ethyl 4, 4-diaryl-4-hydroxybut-2-ynoate which was easily obtained from ethyl propiolate. These colorless compounds show photochromic properties under UV irradiation. The carboxylate group exerts a strong effect on the thermal fading speed of the colored species leading to a fast switch between the colored and colorless states, which, however, can be appropriately counterbalanced leading to a noticeable color change at room temperature. The mechanism of this reversible transformation was studied by NMR. Graphical abstract: Image 1 Highlights: Synthesis of naphthopyrans with an ester function at C-4. Fast and reversible color change upon UV exposure at room temperature. The ester group induces an acceleration of the thermal fading process. NMR studies show the formation of mainly two colored photoisomers.